Lead effects on humans - A Poma, Pedro (2013)
Lead, a metal that has been extensively used since antiquity, can be found in the majority of persons. This metal affects systems, organs, and tissues. The thresholds for its toxic effects vary from individual to individual. Probably because they are in the process of development and due to cer tain physiological, pathological y behavioral characteristics children usually absorb a greater proportion of lead with more severe outcomes than adults. Public health services can identify areas where people has a higher risk for lead intoxication and establish requirements for screening, early diagnosis and adequate treatment. The determination of lead in venous blood is the most sensitive test for the evaluation of lead exposure. Experts recommend maintaining a level below 10 μg/dL. This article reviews origin, effects, diagnosis and treatment of lead intoxication.